Open data infrastructure for resilience analysis: Implementation, examples and case studies in Kenya - Koo, Jawoo; Azzarri, Carlo; Signorelli, Sara; Comanescu, Maria; Guo, Zhe (International Livestock Research Institute, 2016)
This report serves as documentation for the construction, operation and utility of the Horn of Africa Data Catalog (accessible online at http://data.technicalconsortium.org), which was developed to serve as a platform to provide indicators identified as critical to the work of the Technical Consortium for Building Resilience in the Horn of Africa (TC) and its partners. This technical report provides details on the implementation of resilience analytical framework using an open access data and knowledge management platform and presents examples on how to access and visualize them online through the web user interface and the application programming interface (API).